Pergerakkan Darat Ikan Amfibi Andamia heteroptera Bleeker - Nugroho Susanto, Gatot; Ressa utari, Fransisca (Biogenesis: Jurnal Ilmiah Biologi, 2018)
Andamia heteroptera is amphibious fish that walk in land. That behavior used modification fins for terrestrial locomotion. The aim of the research is to know locomotion of A. heteroptera in land and function of fins when used it for locomotion organ. The result shows that A. heteroptera used pectoral fins, pelvic fins, anal fin and caudal fin for locomotion organ. The sucker disk help for the movement. Caudal fin used for base organ when the fish was jump.